DESIGN OPTIMIZATION FOR MAXIMUM EFFICIENCY AND PERFORMANCE - Ramadan, Hamdan; Rozaki, Syahrul Maulana (CATHA SAINTIFICA, 2024)
A clutch is a mechanical component used to connect two shaft together in power transmission system. The main function of a clutch in a transmission system is to transmit power from one shaft to another while adjusting the difference in speed or position between the two. This study aims to calculate the critical parameters of the clutch, such as torque, normal pressure, contact area, required force, and centrifugal force on the clutch shoes. This study produces a normal pressure force of Q = 65.99 kg With a force F that is smaller than the maximum allowable force of 24.67 kg and At a minimum rotation of n = 1500 rpm, the centrifugal force generated is F = 626.23 N with a vertical force in the y direction of F = 313.11 N. While at maximum rotation the centrifugal force increases sharp, namely F = 22184.1 N, with a vertical force in the y direction of F = 11092.05 N. The calculation results show that this clutch design is safe to use by meeting all the parameters that have been set. The impact of this research provides increased energy efficiency, system performance and component life, which supports operational cost savings and reduced emissions. In addition, this research encourages technological innovation, development of local industry, and positive contributions to the environment and society.